Designing 3D topological insulators by 2D-Xene (X = Ge, Sn) sheet functionalization in GaGeTe-type structures. Issue 19 (4th May 2017) - Pielnhofer, F.; Menshchikova, T. V.; Rusinov, I. P.; Zeugner, A.; Yu. Sklyadneva, I.; Heid, R.; Bohnen, K.-P.; Golub, P.; Baranov, A. I.; Chulkov, E. V.; Pfitzner, A.; Ruck, M.; et al.
Abstract : First-principles calculations identify isostructural, layered AXTe (A = Ga, In; X = Ge, Sn) compounds as a host for topological phases. Abstract : State-of-the-art theoretical studies anticipate a 2D Dirac system in the "heavy" analogues of graphene, free-standing buckled honeycomb-like Xenes (X = Si, Ge, Sn, Pb, etc. ). Herewith we regard a 2D sheet, which structurally and electronically resembles Xenes, in a 3D periodic, rhombohedral structure of layered AXTe (A = Ga, In; X = Ge, Sn) bulk materials. This structural family is predicted to host a 3D strong topological insulator with Z 2 = 1;(111) as a result of functionalization of the Xene derivative by covalent interactions. The parent structure GaGeTe is a long-known bulk semiconductor; the "heavy", isostructural analogues InSnTe and GaSnTe are predicted to be dynamically stable. Spin–orbit interaction in InSnTe opens a small topological band gap with inverted gap edges that are mainly composed of the In-5s and Te-5p states. Our simulations classify GaSnTe as a semimetal with topological properties, whereas the verdict for GaGeTe is not conclusive and urges further experimental verification. The AXTe family structures can be regarded as stacks of 2D layered cut-outs from a zincblende-type lattice and are composed of elements that are broadly used in modern semiconductor devices; hence they represent an accessible, attractive alternative for applications in spintronics. The layered nature of AXTe should facilitate the exfoliation of their hextuple layers and manufacture of heterostructures.